Open-label phase 3 study of intravenous golimumab in patients with polyarticular juvenile idiopathic arthritis - Ruperto, Nicolino; Brunner, Hermine I; Pacheco-Tena, César; Louw, Ingrid; Vega-Cornejo, Gabriel; Spindler, Alberto J; Kingsbury, Daniel J; Schmeling, Heinrike; Borzutzky, Arturo; Cuttica, Rubén; Inman, C. J.; Malievskiy, Victor; et al. (Oxford University Press (OUP), 2021)
Objectives: To assess efficacy, pharmacokinetics (PK) and safety of intravenous (i.v.) golimumab in patients with polyarticular-course JIA (pc-JIA). Methods: Children aged 2 to <18 years with active pc-JIA despite MTX therapy for ≥2 months received 80 mg/m2 golimumab at weeks 0, 4, then every 8 weeks through week 52 plus MTX weekly through week 28. The primary and major secondary endpoints were PK exposure and model-predicted steady-state area under the curve (AUCss) over an 8-week dosing interval at weeks 28 and 52, respectively. JIA ACR response and safety were also assessed. Results: In total, 127 children were treated with i.v. golimumab. JIA ACR 30, 50, 70, and 90 response rates were 84%, 80%, 70% and 47%, respectively, at week 28 and were maintained through week 52. Golimumab serum concentrations and AUCss were 0.40 μg/ml and 399 μg day/ml at week 28. PK exposure was maintained at week 52. Steady-state trough golimumab concentrations and AUCss were consistent across age categories and comparable to i.v. golimumab dosed 2 mg/kg in adults with rheumatoid arthritis. Golimumab antibodies and neutralizing antibodies were detected via a highly sensitive drug-tolerant assay in 31% (39/125) and 19% (24/125) of patients, respectively. Median trough golimumab concentration was lower in antibody-positive vs antibody-negative patients. Serious infections were reported in 6% of patients, including one death due to septic shock. Conclusion: Body surface area-based dosing of i.v. golimumab was well tolerated and provided adequate PK exposure for clinical efficacy in paediatric patients with active pc-JIA. ClinicalTrials.gov number NCT02277444
Keywords: Golimumab; Intravenous; Juvenile idiopathic arthritis; Pharmacokinetics; Tumour necrosis factor alpha